2017
DOI: 10.1103/physrevb.96.014413
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and dielectric order in the kagomelike francisite Cu3Bi(SeO3)2O2Cl

Abstract: We report a single-crystal neutron diffraction and inelastic neutron scattering study on the spin 1/2 cuprate Cu3Bi(SeO3)2O2Cl, complemented by dielectric and electric polarization measurements. The study clarifies a number of open issues concerning this complex material, whose frustrated interactions on a kagome-like lattice, combined with Dzyaloshinskii-Moriya interactions, are expected to stabilize an exotic canted antiferromagnetic order. In particular, we determine the nature of the structural transition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…In the second scenario, the transition is between two non-polar phases, with a doubling of the unit cell, and the soft mode is found at the zone boundary in the high-symmetry phase, so that it can no longer be followed by optical spectroscopy techniques. Crystallographic data [21] support the latter scenario, but the former has also been discussed in past spectroscopic studies [23,24]. In order to confirm whether this comes with a mode softening at the zone boundary above T c as anticipated from the structural studies, we performed inelastic X-ray scattering (IXS) to follow the mode at the Z point of the Brillouin zone (See Fig.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…In the second scenario, the transition is between two non-polar phases, with a doubling of the unit cell, and the soft mode is found at the zone boundary in the high-symmetry phase, so that it can no longer be followed by optical spectroscopy techniques. Crystallographic data [21] support the latter scenario, but the former has also been discussed in past spectroscopic studies [23,24]. In order to confirm whether this comes with a mode softening at the zone boundary above T c as anticipated from the structural studies, we performed inelastic X-ray scattering (IXS) to follow the mode at the Z point of the Brillouin zone (See Fig.…”
supporting
confidence: 58%
“…Neutron refinements have established a symmetry descent P mmn −→ P cmn, whereby a mirror plane is replaced with a glide plane [21], which corresponds to the most simple one-dimensional AFE transition [2]. The small but unambiguous dielectric anomaly [21] and the nearly degenerate energies of the non-polar and polar polymorphs [22] tend to confirm the AFE character of the transition. Our study is focused on its lattice dynamics at low frequencies, with the aim to elucidate its driving mechanism.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…For example, J FM of −120 K was reported in CuSe 2 O 5 47 , whereas FM interactions between nearest neighbors in francisite, Cu 3 Bi(SeO 3 ) 2 O 2 Cl 31,48,49 , may also be influenced by the SeO 3 links. The Cu–O–Cu angles of the fracisite structure are, in fact, in the same range of 110–115°, where, according to our results, both FM and AFM interactions may occur depending on the presence or absence of the SeO 3 link.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Recently, it has been reported that incorporation of halides into oxides can strikingly change their electronic structures and modify the physical properties [7][8] . Several novel transition-metal oxychlorides have been reported to date, such as MnSb 4 O 6 Cl 2 [9] , PbCu 2 (SeO 3 ) 2 Cl 2 [10] , Cu 3 Bi(SeO 3 ) 2 O 2 Cl [ 11 ] , FeTe 2 O 5 X (X=Cl, Br) [ 1 2 ] , SrCu 2 (SeO 3 ) 2 Cl 2 [13] , SmSb 2 O 4 Cl [14] , and MSb 2 O 3 (OH)Cl (M=Co, Fe, Mn) [15] . Above-mentioned materials show novel structures and special magnetic properties due to their diversity structural which was more helpful to generate the magnetic ordering during low temperature.…”
mentioning
confidence: 99%